The incremental shuttle walk test predicts mortality in non‐group 1 pulmonary hypertension: results from the ASPIRE Registry. (1st May 2019) - Billings, Catherine G.; Lewis, Robert; Hurdman, Judith A.; Condliffe, Robin; Elliot, Charlie A.; Thompson, A.A. Roger; Smith, Ian A.; Austin, Matthew; Armstrong, Iain J.; Hamilton, Neil; Charalampopoulos, Athanasios; Sabroe, Ian; et al.
Abstract : Pulmonary hypertension (PH) is classified into five groups based on disease etiology but there is only limited information on the prognostic value of exercise testing in non‐group 1 PH. In group 1 PH, the incremental shuttle walking test (ISWT) distance has been shown to correlate with pulmonary hemodynamics and predict survival without a ceiling effect. This study assessed the ISWT in non‐group 1 PH. Data were retrieved from the ASPIRE Registry (Assessing the Spectrum of Pulmonary hypertension Identified at a REferral centre) for consecutive patients diagnosed with PH. Patients were required to have been systematically assessed as group 2–5 PH and to have a baseline ISWT within three months of cardiac catheterization. Patients were stratified according to incremental shuttle walk test distance (ISWD) and ISWT distance percent predicted (ISWD%pred). A total of 479 patients with non‐group 1 PH were identified. ISWD and ISWD%pred correlated significantly with symptoms and hemodynamic severity. ISWD and ISWD%pred predicted survival with no ceiling effect. The test was prognostic in groups 2, 3, and 4. ISWD and ISWD%pred and change in ISWD and ISWD%pred at one year were all significant predictors of outcome. In patients with non‐group 1 PH the ISWT is a simple non‐invasive test that is easy to perform, is predictive of survival at baseline and follow‐up, reflects change, and can be used in the assessment of PH of any etiology.